SLOPE STABILITY ANALYSIS OF THE PATHUK HILL FOR THE RESORTS DEVELOPMENT - Setiawan, Jatmika; Kresna, Bagus Ngurah; Sanjaya, Arya Dwi; Bayu, Adrianus (Universitas Pembangunan Nasional Veteran Yogayakarta, 2015)
Pathuk Hill is located abouth 15km eastern from Yogyakarta City. Pathuk Hill is elongatedhill (escarpment) trending NE-SW stricking and formed the steep slopes to the north-west.An average height of a Pathuk Hill between 200m-250m above sea level. This hill arecomposed by interbadded tufaceous sandstone and tuff of Semilir Formation in the lowerpart. Conformity above of Semilir Formation is volcanic breccia of a solid NglanggranFormation. In the top of the Pathuk Hill we can see the exotic view of Yogyakarta City in thewestern, Merapi Vocano in the north-western and sunset in the western in the afternoon. Inthe Pathuk Hill resort will be development of the big resort as the gateway to the WonosariCity. This area would be developed as a torism object between Yogyakarta City andWonosari City.Keywards : Pathuk Hill, slope tability, resort, view, torism object.